2020
DOI: 10.1175/jas-d-19-0229.1
|View full text |Cite
|
Sign up to set email alerts
|

Size and Structure of Dry and Moist Reversible Tropical Cyclones

Abstract: The size and structure of tropical cyclones (TCs) are investigated using idealized numerical simulations. Three simulations are conducted: a pure dry TC (DRY), a moist reversible TC (REV) with fallout of hydrometeors in the atmosphere disallowed, and a typical TC (CTL). It was found that the width of the eyewall ascent region and the radius of maximum wind rm are much larger in DRY and REV than those in CTL. This is closely related to the deep inflow layer (~4 km) in DRY and REV associated with a different ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In fact, the width of the Hadley cell is seen to decrease with L v , and this seems to be directly connected to the equatorial deformation scale. Further, similar to emerging details on the possibility of warm core cyclones in dry simulations (Mroweic et al, 2011;Cronin and Chavas, 2019;Wang and Lin, 2020), and their implications for real-world cyclonic systems, the effects of varying moist coupling on transient activity could prove to be of use in a more basic understanding of the moist modes of tropical intraseasonal variability.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In fact, the width of the Hadley cell is seen to decrease with L v , and this seems to be directly connected to the equatorial deformation scale. Further, similar to emerging details on the possibility of warm core cyclones in dry simulations (Mroweic et al, 2011;Cronin and Chavas, 2019;Wang and Lin, 2020), and their implications for real-world cyclonic systems, the effects of varying moist coupling on transient activity could prove to be of use in a more basic understanding of the moist modes of tropical intraseasonal variability.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…In all, we believe that these simulations, much like the moist and dry scenarios studied by Frierson et al (2006Frierson et al ( , 2007, will help in a more robust view of planetary atmospheric circulation regimes in the presence of a condensable substance, especially ones with a different latent heat compared to water vapor. Further, even on present-day Earth, our hope is that exploring the effect of different coupling strengths will help in the understanding of moist geophysical systems -much like the dry and moist simulations of tropical cyclones that are yielding insight into the fundamental nature of these cyclonic systems (Mroweic et al, 2011;Cronin and Chavas, 2019;Wang and Lin, 2020). The modeling framework to address these questions is described in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, conditions on Earth with significantly weaker meridional surface temperature gradients (Brierley et al, 2009) might be susceptible to overturning flows driven in this manner. Further, similar to emerging details on the possibility of warm-core cyclones in dry simulations (Mroweic et al, 2011;Cronin and Chavas, 2019;Wang and Lin, 2020) and their implications for real-world cyclonic systems, the effects of varying moist coupling on transient activity could prove to be of use in a more basic understanding of the moist modes of tropical intraseasonal variability.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…In all, we believe that these simulations, much like the moist and dry scenarios studied by Frierson et al (2006;2007), will help in a more robust view of planetary atmospheric circulation regimes in the presence of a condensable substance, especially ones with a different latent heat compared to water vapour. Further, even on present-day Earth, our hope is that exploring the effect of different coupling strengths will help in the understanding of moist geophysical systems -much like the dry and moist simulations of tropical cyclones that are yielding insight into the fundamental nature of these cyclonic systems (Mroweic et al, 2011;Cronin and Chavas, 2019;Wang and Lin, 2020). The modelling framework to address these questions is described in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Sabuwala et al (2015), who did not quote Emanuel (1988), Wang and Lin (2020) used the approach of Emanuel (1988) to account for the total water mixing ratio q t in the pseudoadiabatic model of Emanuel and Rotunno (2011) and found that this reduces air velocity at the radius of maximum wind in a hurricane with reversible adiabats by about 10% (or squared velocity by 20%). At the same time, Emanuel and Rousseau-Rizzi (2020) indicated that the impact of the water lifting on storm intensity depends on the integral of dq t /dt over a closed contour.…”
mentioning
confidence: 99%